Cumulative effects of bamboo sawdust addition on pyrolysis of sewage sludge: Biochar properties and environmental risk from metals. (March 2017) - Jin, Junwei; Wang, Minyan; Cao, Yucheng; Wu, Shengchun; Liang, Peng; Li, Yanan; Zhang, Jianyun; Zhang, Jin; Wong, Ming Hung; Shan, Shengdao; Christie, Peter
Graphical abstract: Highlights: Sludge was pyrolyzed with bamboo sawdust for metal immobilization. Metals were transformed from highly available to stable forms after pyrolysis. Addition of bamboo sawdust in sludge co-pyrolysis minimizes the risk from metals. Co-pyrolysis with bamboo sawdust at 600 °C is suitable for sludge metal stabilization. Abstract: A novel type of biochar was produced by mixing bamboo sawdust with sewage sludge (1:1, w/w) via a co-pyrolysis process at 400–600 °C. Changes in physico-chemical properties and the intrinsic speciation of metals were investigated before and after pyrolysis. Co-pyrolysis resulted in a lower biochar yield but a higher C content in the end product compared with use of sludge alone as the raw material. FT-IR analysis indicates that phosphine derivatives containing PH bonds were formed in the co-pyrolyzed biochars. In addition, co-pyrolysis of sludge with bamboo sawdust transformed the potentially toxic metals in the sludge into more stable fractions, leading to a considerable decrease in their direct toxicity and bioavailability in the co-pyrolyzed biochar. In conclusion, the co-pyrolysis technology provides a feasible method for the safe disposal of metal-contaminated sewage sludge in an attempt to minimize the environmental risk from potentially toxic metals after land application.